Capnocytophaga felis sp. nov. isolated from the feline oral cavity - Suzuki, Michio; Umeda, Kaoru; Kimura, Masanobu; Imaoka, Koichi; Morikawa, Shigeru; Maeda, Ken (International journal of systematic and evolutionary microbiology, 2020)
Four strains, KC07070 T , KC07105, 11 025B-8C and 11 026B-8-C, were isolated from the oral cavity of cats in 2007 or 2011 in Japan. These strains were Gram-stain-negative rods, exhibited gliding motility, grew in air with 5 % CO 2 and showed catalase and oxidase activity. The sequences of 16S rRNA genes of the four strains were 100 % identical. Additionally, the sequences of 16S rRNA genes of KC07070 T had identity to those of the type strains of Capnocytophaga canimorsus (97.7 %), Capnocytophaga cynodegmi (97.8 %) and Capnocytophaga canis (97.4 %) and 91.2–93.8% identity to those of other species of the genus Capnocytophaga . The major cellular fatty acids of KC07070 T were iso-C 15 : 0 (56.2 %) and summed feature 11 (14.9 %). The G+C content of the DNA from KC07070 T was 35.6 mol%, and the genome size was 2.88 Mbp. KC07070 T had digital DNA–DNA hybridization (dDDH) values of 26.2–27.6% and average nucleotide identity (ANI) values of 75.4–83.3 % to the type strains of the closest relatives, C. canimorsus , C. cynodegmi and C. canis . These results of phylogenetic analysis of 16S rRNA gene sequence, cellular fatty acids compositions and dDDH and ANI values indicate that strain KC07070 T represents a novel species, for which we propose the name Capnocytophaga felis sp. nov., with type strain KC07070 T (=JCM 32681 T =DSM 107251 T ).